Motility characterization of albumin sexed spermatozoa in two different diluents and additional antioxidant - Ratnawati, D.; Luthfi, M.; Pamungkas, D.; Affandhy, L. (Journal of the Indonesian Tropical Animal Agriculture, 2020)
The purpose of this study was to characterize spermatozoa motility of sexed semen (X and Y) using albumin by diluents and antioxidant treatments. The material used in this study was fresh semen of Ongole Crossbreed (OC) bull with progressive motility >70%. The sperm sexing methodology used albumin gradient of 5%, 10%, and 15%. The diluents used were CEP-2 and andromed with or without the addition of 1mM Glutathione as an antioxidant. The sexed semen was made into liquid semen and stored at 3-5°C. The motility was observed at day 0 (H0) and day 5 (H5). Motility was analyzed using SCA v.2.1. The parameters measured were total motility, progressive motility, VCL, VSL, VAP, LIN, STR, WOB, ALH, BCF and sperm hyperactive. The experimental applied was the factorial pattern 2 x 2. The first factor was the type of diluents (CEP-2 and Andromed), and the second factor was additional glutathione (with or without). Data was analyzed by general linear model of SPSS-IBM 24 program. Sexed semen with CEP-2 diluents showed better motility of spermatozoa than andromed in the upper layers (spermatozoa X) and lower layers (spermatozoa Y). The CEP-2 diluent had a big role to maintain motility, progressive motility and velocity spermatozoa during cold storage. The addition of Glutathione 1mM could support the motility of sexed spermatozoa at cold storage, especially for LIN, STR, and WOB values.